METHODOLOGY OF FORMATION OF STUDENTS' COMPOSITIONAL THINKING SKILLS IN SCHOOL VISUAL ARTS CLASSES. (Multidisciplinary Journal of Science and Technology, 2024)
Art is a component of human spiritual culture. It includes other types such as music, theater, cinema, fiction, choreography, visual and applied decorative arts. Fine art is one of the types of art that quickly affects the human mind, awakens good feelings in it, inspires a person and enriches his spiritual world. At the same time, visual art is also an educator that helps in the formation and perfection of human personality.